Project maintenance: success factors of project team / Aisyah Ibrahim - Ibrahim, Aisyah (2013)
This study is to investigate on success factor of project team in managing Enterprise Resource Planning (ERP) maintenance project in ERP maintenance stage. A case study on Integrated Management System (IMS) was carried out at Universiti Malaysia Pahang (UMP), Pekan, Pahang Darul Makmur in last April 2012. Interviews sessions were conducted with three key persons from PTMK technical team members to collect staffs experiences in maintenance activities. Data collected from this case study was transcribed and analyzed. Based on the findings, the key people who are the drivers and their roles in maintenance success in ERP Maintenance stage are identified. The interrelationships between the factors which drive the success were synthesized. As results, preliminary models of ERP maintenance is proposed based on empirical data collected from three UMP technical staffs' s experiences and lessons learned of IMS case study.